(untitled) (European Journal of Health Research, 2017)
The social psychology has provided multiple evidences of how certain forms of comparison with other people can improve the welfare and increases the successful coping with different problems and life changes. However, most of these studies have focused on young people and in middle age. The objective of present work is to analyze the social comparison strategies used by aged people living in retirement homes and the related welfare. To do this we have worked with a sample of 30 elderly adults living in retirement homes. The strategies of social comparison and the subjective well-being were measured. Results. The residents used fewer social comparison strategies than non-residents. In addition, residents used less the downward comparisons. On the other hand, our results confirm that the use of adaptive social comparisons relates to high levels of well-being. Conclusions. The social comparisons can improve the welfare during elderly. On the other hand, the downward comparisons acquire a special significance in the residential environments. Discussion. We interpret the positive relations between the use social comparisons and health during elderly from the model of Contrast-Identification. Additionally, we discuss the adaptive value of the under-use of the downward comparisons and its implications in the aging process.